The 7 Habits of Highly Effective Families - Covey, Stephen R. (Golden Books Publishing Co., Inc., 1997)
This book presents a practical and philosophical guide to solving the problems-large and small, mundane and extraordinary-that confront all families and strong communities. It also shows how and why families should have meetings, the importance of keeping promises, how to balance individual and family needs, and how to move from dependence to interdependence.
Keywords: Non-Fiction / Family / Communication in the family / Parent and Child